Estudo experimental de fatores nutricionais na formação de cristais na urina: avaliação do papel da cristalúria na prática clínica - Silva, Sônia Leite da (1996)
As nephrolithiasis results in significant morbidity it has been the subject of epiderniological studies which have shown its increasing prevalence in industrialized countries. Changes in aiimentary pattems have contributed to the evolution of this disease. This study comprises three steps and aims to evaluate some nutritional aspects in calcium-oxalate (CaOx) crystalluria and to assess therole of crystalluria in the clinicai practice. Step 1. An experimental pilot study was undertaken in order to validate a model for the induction of hyperoxaluria in animais. In such model, hyperoxaluria should be kept stable and should be reproducible, and not lead to renal failure. Twelve adult male Wistar AF rats were placed on a Ca-deficient diet (0,1%), receiving a mineral water containing 78 mg/1 of Ca (Evian®), ad libfíum, for 21 days. After a seven-day period of adaptation to the metabolic cage, animais were separated into 6 groups receiving either ethylene-glycol (EG) or sodium oxalate (NaOx) in addition to their diet, for a 15-day period: group I - EG 2.0% (n=2), group II - EG 1.0% (n=2), group III - EG 0.5% (n=2), group IV - Na-Ox 80mg/100 mg (n=2), group V - NaOx 40 mg/100 mg (n=2), group VI - Na-Ox 20mg/100 mg (n=2). Determination of crystalluria, measurements of urinary calcium and oxalate, and plasma creatinine were performed on days 7 and 21. Animais were sacrified at the end ofthe study period; the urinary tract was cautiously dissected in order to detect stone formation, and the kidneys were then harvested for radiologic and histological analysis. A wide toxicity of EG was seen at 2.0% and 1.0% concentratíons, nephrotoxicity being observed at 0.5% concentration. Na-Ox-rich diet induced an increase in oxaluria and the formation of CaOx ciystals. Results were more stable when NaOx 20 mg/100 mg was employed. Step 2. Forty adult male Wistar rats were placed in metabolic cages on a Ca-deficient diet (0.1%) for? days and then on a Ca-deficient, Na-oxalate (NaOx) enriched diet (20 mg/100 g) for another 14 days. The animais were subdivided into three groups receiving three different types of mineral water: group I (n=13), Badoit®, (Ca 222 mg/1); group II (n=14), Contrexéville® (Ca 467 mg/1); and group III (n=13), Evian® (Ca 78 mg/1). Another series of 25 rats (group I, n=9; group II, n=8; group III, n=8) underwent the same study protocol, except that they received a normal Ca diet (1%). On the low-Ca diet, urinary CaOx monohydrate (COM) ciystals were observed only under the NaOx diet, with a mean crystal number signifícantly greater in group III (16.7 ±4.5 crystals/irmP) than in group I or II rats (2.5 ± 1.5 or 4.1 ± 1.5 crystals/mmm^, respectively). Urinary Ca concentrations decreased in all groups (p<0.001) under the NaOx diet, while urinary oxalate concentrations increased in all groups (p< 0.001).